Impact of Environmental Factors on the Academic Performance of Learners in Primary Schools of Nalwanza Sub-county, Bududa District - Stephen Nabalula (Uganda Christian University, 2024)
This study examined the impact of environmental factors on the academic performance of learners in primary schools in Nalwanza Sub-county, Bududa District. The study was guided by the objectives; i) to examine the physical factors affecting the teaching learning process, Bududa District, ii) to analyse the social environmental factors affecting academic performance of learners and iii) to suggest the solutions that can help to curb up examine the effect of the environmental factors that affect the academic performance. The study used a descriptive research design with mixed methods that are both qualitative and quantitative approaches in nature. The study sampled five (5) schools, both government and private out of the many in the Sub-county. The sample size of the study comprised 80 respondents and these were (36) teachers, (32) learners, (19) parents and (5) head teachers using Kjercie and Morgan’s population table in appendix V. The sampling techniques were used to select the respondents were purposive sampling, convenient and simple random sampling techniques. The sampling techniques that were used to select the respondents were purposive sampling, convenient and simple random sampling techniques. The results from the findings of objective one presented by the respondents showed that the leading physical school environmental factors are instructional materials and was reported by 20(25%). Objective two found out that social based factors which were represented by 16(20%) of the respondents showed it is triggered by teacher-pupil relationships. Majority of the respondents represented by 21(26.25%) indicated that environmental education be included in the curriculum. The study concluded that; school environmental factors greatly affect the academic performance of learners in all aspects. The researcher recommended that sensitisation of parents, teachers and learners should be carried out with regard to environmental protection and management in order to strengthen legal and policy for where our children learn.
Undergraduate research